Cave millipeds of the United States. VIII. New genera and species of polydesmidan millipeds from caves in the southwestern United States (Diplopoda, Polydesmida, Macrosternodesmidae) - Shear, William A.; Taylor, Steven J.; Wynne, J. Judson; Krejca, Jean K. (Zootaxa, 2009)
Four new species of presumed troglobitic polydesmidan millipeds in two new genera are described from caves in the states of Arizona, Nevada and California. Pratherodesmus, n. gen., is comprised of the type species, P. voylesi , n. sp., P. ecclesia, n. sp., and P. despaini, n. sp. The genus is found in Arizona and California. Nevadesmus ophimontis, n. gen., n. sp., is from White Pine Co., Nevada; the new genus also includes N. hubbsi (Chamberlin) 1943, new combination. All four species were collected in or near United States National Parks, Bureau of Land Management lands, and in a private preserve. All new taxa are authored by W. A. Shear only.